2023
DOI: 10.1002/pd.6327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of circulating maternal placenta growth factor levels and sonographic evaluation of patients with abnormal first trimester screening analytes

Abstract: Objective: To evaluate the role of mid-trimester placental growth factor (PlGF) in patients with abnormal circulating levels of first-trimester biomarkers.Methods: Retrospective cohort study including singleton pregnancies complicated by abnormal first-trimester biomarkers (2017-2020). Pregnancies complicated with chromosomal/structural anomalies were excluded. All patients had ultrasound imaging including uterine artery Doppler combined with measurement of maternal circulating PlGF. Sonographic findings, mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…PlGF levels significantly affected time to PTB. Median survival time when PlGF was <100 ng/L was reduced to 26 days (95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] for the entire FGR cohort, 26 days (95% CI 15-32) for early FGR, 38 (95% CI 8-72) for late FGR and 40 days (95% CI 15-55) for the AGA group. Multivariable Cox proportional hazard models revealed that women with PlGF <100 ng/L were more than 21 times more likely to have a PTB compared with those with PlGF ≥100 ng/L (HR 21.47, 95% CI 7.91-58.26) in the FGR cohort and nearly four times the AGA cohort (HR 3.85, 95% CI 1.68-8.81) (Table 2).…”
Section: R E Su Ltsmentioning
confidence: 99%
See 2 more Smart Citations
“…PlGF levels significantly affected time to PTB. Median survival time when PlGF was <100 ng/L was reduced to 26 days (95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] for the entire FGR cohort, 26 days (95% CI 15-32) for early FGR, 38 (95% CI 8-72) for late FGR and 40 days (95% CI 15-55) for the AGA group. Multivariable Cox proportional hazard models revealed that women with PlGF <100 ng/L were more than 21 times more likely to have a PTB compared with those with PlGF ≥100 ng/L (HR 21.47, 95% CI 7.91-58.26) in the FGR cohort and nearly four times the AGA cohort (HR 3.85, 95% CI 1.68-8.81) (Table 2).…”
Section: R E Su Ltsmentioning
confidence: 99%
“…Similarly, the sFlt-1/PlGF ratio significantly affected time to PTB. Median survival time for women with an abnormal sFlt-1/PlGF ratio was reduced to 28 days (95% CI 15-39) in the overall FGR group, 26 days (95% CI for in the early FGR, 62 (95% CI 10-106) in the late FGR and 29 days (95% CI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] in the AGA cohorts. Multivariable Cox proportional hazard models revealed that women with a raised sFlt-1/PlGF ratio were nearly seven times as likely to have a PTB (HR 6.91, 95% CI 3.43-13.92) in the FGR cohort and almost six times as likely in the AGA cohort (HR 5.65, 95% CI 2.35-13.61) (Table 2).…”
Section: R E Su Ltsmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental dysfunction is associated with an imbalance in placentally derived pro-and anti-angiogenic factors. Low levels of placental growth factor (PlGF), a strongly proangiogenic hormone, and elevated levels of its antiangiogenic counterpart, soluble fms-like tyrosine kinase-1 (sFlt-1) 17,18 , as well as an increased sFlt-1/PlGF ratio are seen in women with pre-eclampsia and FGR, and are reflective of placental dysfunction 17,[19][20][21][22] . Although there is some evidence that maternal PlGF levels and the sFlt-1/PlGF ratio may be helpful in predicting timing of delivery and rate of disease progression in pregnancies complicated by FGR [23][24][25][26][27] , there are limited data regarding their association with, or potential for, prediction of PTB beyond their utility in screening 28,29 and diagnosis 30,31 of adverse outcome 24,32,33 in women with pre-eclampsia or FGR.…”
Section: Introductionmentioning
confidence: 99%